(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Civil aviation is always the silver bullet target of the terrorist due to countless favorable reason for them. The World Trade Center attack on September 11, 2001, was an eye-opener for the law enforcement agencies across the world. Numeroussophisticated technologies and resources pumped in to keep civil aviation safe to avoid another airborne catastrophe and the world community succeeds to a certain extent as well. However the augmentation of stringent security increases the woes of the passenger at airport and sometimes valuable customer feels they are considered as suspected terrorist. Travelers today demand quick clearance and greater convenience. The outbreak of Covid-19, adds one more misery. But exponential growth of passenger and inundated infrastructure always create obstacle in this direction. This paper discusses about the solutions to the aforementioned dilemma in certain extent, and proposes new processes and alternatives that simultaneously satisfy both passenger and security.